THE INFLUENCE OF EMPLOYEE DISCRETION ON THE RATIONALIZATION OF UNETHICAL BEHAVIOR IN LAND ADMINISTRATION - Abdul Azis; Andy Alfatih; Muhammad Nur Budiyanto; Raniasa Putra (RADJA PUBLIKA, 2026)
Land administration services frequently face integrity challenges due to the high discretionary power required by frontline officials. This study aims to investigate the influence of employee discretion on the rationalization of unethical behavior and the moderating role of public service motivation. A cross-sectional survey was conducted among two hundred and ninety-two civil servants and contract workers in regional land administration offices. Data were collected using vignette-based scenarios to mitigate social desirability bias and analyzed using partial least squares structural equation modeling. The findings reveal that increased discretionary power significantly heightens the propensity of employees to cognitively justify unethical actions. Conversely, intrinsic motivation to serve the public significantly reduces this tendency. Crucially, the analysis confirms that motivation acts as a quasi-moderator; it effectively buffers and weakens the negative impact of operational discretion on ethical rationalization. The study also uncovered an adversarial posture toward oversight bodies, which emerged as the most dominant neutralization technique among officials. Furthermore, significant differences in ethical resilience were observed between permanently tenured staff and contract workers. Cultivating intrinsic public values is essential to prevent operational flexibility from mutating into systemic corruption. Institutional integrity requires continuous ethical socialization alongside robust accountability frameworks.